HUBUNGAN PEMANFAATAN BUKU KESEHATAN IBU DAN ANAK DENGAN KETERATURAN KUNJUNGAN PEMERIKSAAN KEHAMILAN DI PUSKESMAS AMPENAN TAHUN 2021 - Putri, Ema; Kardi, Kardi (Aspiration of Health Journal, 2023)
Based on the result of a preliminary study that has been carried out on the register data for pregnant mothers at UPTD of Ampenan Public Health Center from 2021 showed a decrease from previous years. Visits of pregnant mothers recorded a total of 420 pregnant mothers’ visits decreased by 24.28% from the previous year’s achievement of 523 pregnant mothers. Restriction of health service have an impact on health, education, information, and education received by pregnant mothers. This research is descriptive using a cross sectional approach, the population is 420 pregnant mothers and the sample of this study was taken by accidental sampling and calculated using Slovin formula as many as 81 pregnant mothers. The independent variable was the utilization of maternal and child health book while dependent variable was regularity of pregnancy visits. The instrument uses a questionnaire. Data analysis using univariate analysis using frequency distribution test, bivariate analysis of contingency coefficients. Based on the result of analysis between the utilization of maternal and child health book and the regularity of antenatal care visits, it showed a value (p value) = 0.000 <a 0.05 (significant). The test showed that there was a significant relationship between the utilization of maternal and child health book and the regularity of antenatal care visits. It can be concluded that there is a significant relationship between the utilization of maternal and child health book and the regularity of pregnancy visits. It suggested to Ampenan Public Health Center to convey the health workers related to the use of regular pregnancy check-ups.